Population-based breast cancer screening in Pavia (northern Italy) in 2016-2018: Key performance indicators and sensitivity estimate - Deandrea, Silvia; Manzoni, Federica; Tanious, Marina; Parrini, Andrea; Crema, Marinella; Perotti, Pietro; Dalle Carbonare, Simona; Magenes, Giancarlo; Cadum, Ennio; Boschetti, Lorenza; Marguati, Stefano; Cecconami, Lorella; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: This study aims to assess the quality of the population-based breast cancer screening programme in Pavia, northern Italy computing its key performance indicators and estimating its sensitivity for the years 2016-2018. Methods: Invitation and examination coverage, participation rate, recall rate, detection rate and positive predictive values were computed on the basis of data provided yearly to the Italian Ministry of Health. Sensitivity was estimated identifying interval cancers in the local Cancer Registry and computed with the proportional incidence method. Results: In 2016-2018 the adjusted invitation coverage was 90%, and the adjusted participation rate was 62%. Recall rate was 8.4% for first screenings and 3.9% for subsequent ones. The number of screen-detected cases was 268, corresponding to a detection rate of 6.6‰ for first screenings and 4.6‰ for subsequent screenings. The number of interval cancers observed was 110 over the study period; the proportional incidence was 22% for the first interval year and 50% for the second interval. The overall sensitivity of the screening program was 64%. Conclusions: The analysis of performance indicators and sensitivity estimates for the Pavia programme indicates that the programme performance is in line with the quality standards set by the European Union and the Italian reference scientific society (GISMa).